PENGARUH MODEL PEMBELAJARAN CONTEXTUAL TEACHING AND LEARING (CTL) TERHADAP HASIL BELAJAR SISWA PADA MATERI TRANSFORMASI GEOMETRI DI KELAS XI MIPA SMA NEGERI 1 TINOMBO - Dwimarni Mukhaera; Bakri M.; Afdalul Rahman (Universitas Tadulako, 2025)
This study was conducted to determine the influence of the Contextual Teaching and Learning (CTL) learning model on student learning outcomes in the Geometry Transformation material in class XI MIPA SMA Negeri 1 Tinombo. This type of research is a Quasi-experimental study with a Posttest-only control group design. The population in this study were all students of XI MIPA SMA Negeri 1 Tinombo totaling 114 students. The sampling technique used was the random sampling technique. The sample in this study was class XI MIPA 4 as the experimental class with 28 students and students of XI MIPA 2 as the control class with 29 students. Testing of research data using one-sided t-test statistical analysis with prerequisite tests, namely normality and homogeneity tests. The results of data analysis obtained in the experimental 79.14 and the control class was 61.56, The results of the calculation of the chi-square normality test data for the experimental class obtained = 4.761 and = 7.81472 and for the control class obtained = 3.478 and = 7.81472. And for the hypothesis value obtained and . With a significance level of α = 5% = 0.05. The results show that Ho is rejected and is accepted, so it can be concluded that the Contextual Teach and Learn (CTL) learning model has a better effect than the direct learning model on student learning outcomes in geometric transformation material.